Neidhart: Selected Songs from the Riedegg Manuscript : Berlin, Staatsbibliothek Preussischer Kulturbesitz, mgf 1062 - Neidhart, von Reuenthal, active 13th century; Wenzel, Edith; Starkey, Kathryn (Book collections on Project MUSE., 2016)
"A translation and commentary on selected songs attributed to the satirical Middle High German poet Neidhart from the thirteenth-century Riedegg manuscript"--